Coordination between Federal and Provincial Governments in Implementing the National Action Plan (NAP): Challenges and Successes - Ullah, Waseem; Razzaq Khan, Saima; Marwat, Imran Ullah Khan (The Lighthouse Journal of Social Sciences, 2024)
The National Counter Terrorism Action Plan (NAP) introduced in 2014 is a major policy of the Government of Pakistan for counter-terrorism with multi sector representation from federal and provincial authorities. This study explores the structural, political and operating issues that emerge in this relationship and assesses the difficulties and achievements of realising the security objectives of NAP. Due to the use of qualitative data collection techniques, this study aims to explore the various plans and challenges the federal and provincial authorities undergo when implementing NAP. This paper describes how all these governmental layers work together towards the achievement of NAP security objectives while identifying documented integration scenarios that have positively impacted security. Moreover, the study gives examples of the federal and provincial government cooperation in the fight against the threats, showing that this cooperation helps to achieve the results in increasing people’s safety and decreasing terrorism occurrences. Also, this study provides prescription on how to enhance intergovernmental relations for better counter-terrorism operations. The following recommendations are intended to enhance better coordinated policy adoption and implementation to meet present and future counter-terrorism threats. Finally, the study helps to provide important conclusions for increasing efficiency of federal-provincial cooperation within the context of NAP, which points to the crucial importance of increased communication, exchange of resources, and development of the federal strategy for counter-terrorism in provinces.